2018
DOI: 10.3846/20294913.2016.1218372
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Semiconductor Industry Based on a Metafrontier Approach

Abstract: Abstract. The semiconductor industry has been regarded as one of the most important industries by Taiwan due to the market share of Taiwan's semiconductor industry in 2011 ranked second worldwide. However, the European debt crisis triggered a global economic recession in 2011, causing Taiwan's output of semiconductors in 2010 and 2011 to show negative growth. This paper will mainly explore, from the performance evaluation perspective, the Malmquist productivity index of the Taiwan's semiconductor industry base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…(2) Based on the analysis result of operation performance of enterprises during different periods using productivity index, mean total factor productivity change declined within the range of (0.873, 0.996), which indicates material impact of the financial crisis. This result is consistent with the research result of Chiu et al [3]. Mean total factor productivity change greatly increased within the range of (1.098, 1.145) during the period between 2011 and 2012, but further declined within the range of (0.660, 0.725) during the period between 2013 and 2015, and further increased within the range of (1.313, 1.529) during the period between 2016 and 2017.…”
Section: A Contributionsupporting
confidence: 94%
See 4 more Smart Citations
“…(2) Based on the analysis result of operation performance of enterprises during different periods using productivity index, mean total factor productivity change declined within the range of (0.873, 0.996), which indicates material impact of the financial crisis. This result is consistent with the research result of Chiu et al [3]. Mean total factor productivity change greatly increased within the range of (1.098, 1.145) during the period between 2011 and 2012, but further declined within the range of (0.660, 0.725) during the period between 2013 and 2015, and further increased within the range of (1.313, 1.529) during the period between 2016 and 2017.…”
Section: A Contributionsupporting
confidence: 94%
“…This result is consistent with the research result of the reference [15]. Further, prior studies, including Lee and Pai [2], Wang et al [15], and Chiu et al [3], argue that more R&D inputs will 12 facilitate growth of enterprises and will have deferred effects on their future performance [7]. However, this study found insignificant relation between R&D expense and operation performance.…”
Section: B Managerial Implicationssupporting
confidence: 89%
See 3 more Smart Citations